Analysis of office rent determinants based on spearman correlation / Thuraiya Mohd, Muhamad Harussani and Suraya Masrom - Mohd, Thuraiya; Harussani, Muhamad; Masrom, Suraya (2022)
This study presents the relation between office rent determinants and rental values in the Kuala Lumpur office market. The datasets comprise office rental transactions acquired from the Valuation and Services Department from year 2015 until 2021, prioritising Kuala Lumpur city centre were analysed. Based on the 538 rental transactions, inferential statistics were employed to analyse the relationship between the rent determinants grouped into 5 (five) categories, locational, physical, macroeconomics, lease details and certifications. By employing the Spearman Correlation analysis, this study identified the statistical relation of office rent determinants towards the rental values, through the consideration of the correlation coefficient value of 'Rs'. The results indicate that office rent determinants such as amenities and in-house services and green certificates positively react to the office rental values. Nonetheless, the analysis conducted demonstrates that from 17 included determinants, most of it appears to have a weak relation to rental values. This study will provide new insight for property investors by considering these determinants to base their investment decision-making.